EFFECT OF MICROENCAPSULATED Lactobacillus sp. ON CATFISH (Pangasius hypophthalmus) INFECTED WITH Aeromonas sp. - Kharima, Zhafira Putri; Mulyani, Yuniar; Iskandar, Iskandar; Herman, Roffi Grandiosa (Jurusan Perikanan dan Kelautan, 2024)
The prevention of fish infections caused by Aeromonas sp. bacteria can be achieved using Lactobacillus sp. bacteria. This study aims to identify and analyse the effect of Lactobacillus sp. using the microencapsulation method to treat catfish infected with Aeromonas sp. The identification of Lactobacillus sp. bacteria was conducted through microbiological and molecular tests. After obtaining the test results, the research continued with the application of microencapsulation using the emulsion technique. The impact of this microencapsulation was evaluated on catfish through an experimental approach employing a completely randomised design (CRD), with 10 catfish tested in each experimental aquarium. The study included five treatments, designated as A, B, C, D, and E. Treatment A served as the control, without the administration of Lactobacillus. Treatment B involved the application of Lactobacillus without microencapsulation. Treatments C, D, and E utilised varying doses of Lactobacillus at 0.003, 0.005, and 0.007 g/L, respectively. Each treatment was conducted in triplicate. Microbiological and molecular testing identified encapsulated Lactobacillus sp., specifically Lactobacillus helveticus and Lactobacillus johnsonii. The results indicated that treatment D, comprising a dose of 0.005 g/L of Lactobacillus helveticus and Lactobacillus johnsonii, was the most effective in promoting the healing of catfish infected with Aeromonas hydrophila bacteria.Keywords: Completely randomized design, bacterial infection mitigation, probiotic bacteria, emulsion technique.